Boron/nitrogen co-doped diamond electrode for highly efficient electrochemistry detection of aniline. Issue 1 (2nd January 2021) - Li, Jiahan; Wang, Qiliang; Liu, Yaofeng; Jiang, Zhigang; Liu, Junsong; Li, Hongdong; Yuan, Xiaoxi
Abstract: Aniline is a mutagenic and carcinogenic material for human health, and it is desirable to construct high-performance detecting system for the trace detection of aniline. In this work, the boron (B)/nitrogen (N)-doped diamond (BND) films prepared by chemical vapor deposition are proposed as electrochemical electrodes to detect aniline in a wide concentration scale. The BND electrodes have a high sensitivity (detect limitation of 0.29 μmol L −1 ) and a wide linear detection range (0.5 − 500 μmol L −1 ). Both the detection limitation and linear range are significantly improved with respect to that from traditional electrodes of boron-doped diamond and various carbonaceous materials, which can be attributed to the synergistic effect of increased electrochemistry reduction and density of reaction sites on the BND electrode surfaces. This work develops a kind of electrochemical electrodes of B/N-doped diamond films with high performances for quantitative detections of aniline in practical applications. Supplemental data for this article is available online at http://dx.doi.org/10.1080/26941112.2021.1939170